INTERAKSI DEMOKRATIS LINTAS JENJANG MAHASISWA MELALUI PEMBELAJARAN TEMATIK-EKSPLORATIF-DEMOKRATIK DALAM BELAJAR FISIKA DI AIR TERJUN TUMIMPERAS - Mulyono, Maulana; Palilingan, Rolles Nixon; Tumimomor, Farly Reynol; Lahope, Kenny Setiawan (LPPM Politeknik Saint Paul Sorong, 2024)
The study is motivated by the importance of paying attention to democratic interaction among students in order to prepare them with the 21st-century competencies they need to possess. This research aims to understand the democratic interactions across different levels of students through Thematic-Explorative-Democratic Learning in physics at Tumimperas Waterfall. The research method used is descriptive qualitative, with the subjects of the study being two groups of students from the Physics Department at Manado State University. Data were collected through observation and peer assessment based on eight indicators of democratic interaction. Data were analyzed through data collecting, reduction, display, and classification. The results showed that students from various levels were able to interact democratically with scores ranging from good to very good. This democratic interaction aids in the development of critical thinking skills, collaboration, effective communication, and social responsibility. Thus, Thematic-Explorative-Democratic Learning at Tumimperas Waterfall can be considered an effective learning activity in developing 21st-century competencies in students